2003
DOI: 10.1104/pp.011296
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Effects of Free-Air CO2Enrichment (POPFACE) on Leaf Growth, Cell Expansion, and Cell Production in a Closed Canopy of Poplar

Abstract: Leaf expansion in the fast-growing tree, Populus ϫ euramericana was stimulated by elevated [CO 2 ] in a closed-canopy forest plantation, exposed using a free air CO 2 enrichment technique enabling long-term experimentation in field conditions. The effects of elevated [CO 2 ] over time were characterized and related to the leaf plastochron index (LPI), and showed that leaf expansion was stimulated at very early (LPI, 0-3) and late (LPI, 6-8) stages in development. Early and late effects of elevated [CO 2 ] w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
67
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 46 publications
9
67
0
1
Order By: Relevance
“…Moreover, the growth patterns we observed are consistent with other leaf growth analyses, which have shown a similar proximodistal gradient in growth rates in Arabidopsis (Wiese et al, 2007) as well as in other species, such as tobacco (Nicotiana tabacum; Avery, 1933;Poethig and Sussex, 1985;Walter and Schurr, 1999;Walter et al, 2003), sunflower (Helianthus annuus; Granier and Tardieu, 1998), grape (Vitis vinifera; Wolf et al, 1986), spinach (Spinacia oleracea; Saurer and Possingham, 1970), cocklebur (Xanthium pensylvanicum; Maksymowych, 1959;Erickson, 1966), ivy (Hedera helix; Wang et al, 2011), and poplar (Populus spp. ; Taylor et al, 2003). An exception to this pattern was shown in soybean (Glycine max; Ainsworth et al, 2005), where no spatial gradient was observed, leading the authors to conclude that the mechanisms of leaf growth in soybean may be different from that in other species.…”
Section: Accuracy and Reliability Of The Methods And Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, the growth patterns we observed are consistent with other leaf growth analyses, which have shown a similar proximodistal gradient in growth rates in Arabidopsis (Wiese et al, 2007) as well as in other species, such as tobacco (Nicotiana tabacum; Avery, 1933;Poethig and Sussex, 1985;Walter and Schurr, 1999;Walter et al, 2003), sunflower (Helianthus annuus; Granier and Tardieu, 1998), grape (Vitis vinifera; Wolf et al, 1986), spinach (Spinacia oleracea; Saurer and Possingham, 1970), cocklebur (Xanthium pensylvanicum; Maksymowych, 1959;Erickson, 1966), ivy (Hedera helix; Wang et al, 2011), and poplar (Populus spp. ; Taylor et al, 2003). An exception to this pattern was shown in soybean (Glycine max; Ainsworth et al, 2005), where no spatial gradient was observed, leading the authors to conclude that the mechanisms of leaf growth in soybean may be different from that in other species.…”
Section: Accuracy and Reliability Of The Methods And Resultsmentioning
confidence: 78%
“…Early efforts to measure leaf growth involved drawing ink dots on the adaxial leaf surface to delineate a grid of small rectangles whose deformations over time could be used to calculate regional growth rates (Avery, 1933;Richards and Kavanagh, 1943). Other studies since then have employed the same concept of quantifying growth at the adaxial leaf surface by tracking ink marks (Maksymowych, 1962;Saurer and Possingham, 1970;Poethig and Sussex, 1985;Granier and Tardieu, 1998;Wang et al, 2011) or vein intersections (Maksymowych, 1959;Erickson, 1966;Wolf et al, 1986;Walter and Schurr, 1999;Taylor et al, 2003;Walter et al, 2003). Recently, digital image sequence analysis tools have been developed to automatically track the displacement of identifiable features in successive images of a leaf (Schmundt et al, 1998;Ainsworth et al, 2005;Wiese et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased leaf growth, leading to larger individual leaf size, is one component of increased LAI measured at elevated [CO 2 ] in field experiments (Taylor et al, 2003;Tricker et al, 2004;Dermody et al, 2006). At the molecular level, the basis for changes in LAI at elevated [CO 2 ] is largely unknown.…”
mentioning
confidence: 99%
“…At the molecular level, the basis for changes in LAI at elevated [CO 2 ] is largely unknown. Both cell production rates and cell expansion have been shown to be sensitive to elevated [CO 2 ] (Taylor et al, 1994(Taylor et al, , 2003. Transcript analysis of growing poplar (Populus spp.)…”
mentioning
confidence: 99%